Longitudinal Trends and Drivers of Antimicrobial Resistance in Campylobacter Worldwide (1954-2023) - Shulei Jia; Xuebin Xu; Mengqi Qu; Yuhang Pei; Siqi Sun; Yue Liu; Wanting Dong; Yongfei Hu; Baoli Zhu; George F. Gao; Yanan Wang (Zoonoses)
<!-- named anchor --> Objective: The zoonotic pathogen Campylobacter is a major foodborne bacterial species worldwide. The distribution and drivers of antimicrobial resistance (AMR) in global Campylobacter strains remain largely unknown. Therefore, a comprehensive analysis of longitudinal trends and driving factors of AMR in Campylobacter is necessary at a global level. <!-- named anchor --> Methods: We downloaded from public repositories 66,771 Campylobacter genomes (24,115 from C. coli and 42,656 from C. jejuni) in 53 countries/regions during 1954–2023, and performed a comprehensive analysis. <!-- named anchor --> Results: We categorized the Campylobacter isolates into 2,771 sequence types (STs), 45 of which were shared among humans, chickens, pigs, cattle, and the environment. We uncovered the spatial and temporal characteristics of resistance across antimicrobial classes on a global scale, and observed increased trends in the aminoglycoside, tetracycline, and fluoroquinolone resistance of C. jejuni during the past 23 years. Some of the antibiotic, climate, and socioeconomic indicators collected from the World Bank might potentially have driven the rise of AMR in various countries/regions to varying degrees. <!-- named anchor --> Conclusions: In summary, we present a global genetic atlas of Campylobacter, which provides valuable insights for understanding the transmission dynamics of AMR in this species.